Social Identity and Financial Investment Decisions: Empirical Insights on German-Turks - Stumpfegger, Eva (Springer, 2015)
​This book investigates how social identity relates to financial investment behavior of the German-Turkish diaspora. The author approaches this study using qualitative research and multiple semi-structured in-depth interviews with a strong philosophical and methodological basis. Taking a phenomenological stance, the empirical results reveal many nuanced shades of bi-cultural identity. Key findings include a range of social creativity behaviors, also offering an extension to social identity theory by means of re-defining relevant in-groups. Financial investments are considered a family affair, with children being heavily involved and support of (extended) family is defined as investment. Within that realm, German social identity prevails with regard to financial investments.